2022
DOI: 10.1111/ene.15373
|View full text |Cite
|
Sign up to set email alerts
|

Tau and neurofilament light‐chain as fluid biomarkers in spinocerebellar ataxia type 3

Abstract: Background and purpose Clinical trials in spinocerebellar ataxia type 3 (SCA3) will require biomarkers for use as outcome measures. Methods To evaluate total tau (t‐tau), glial fibrillary acidic protein (GFAP), ubiquitin carboxy‐terminal hydrolase L1 (UCHL1) and neurofilament light‐chain (NfL) as fluid biomarkers in SCA3, ATXN3 mutation carriers (n = 143) and controls (n = 172) were clinically assessed, and the plasma concentrations of the four proteins were analysed on the Simoa HD‐1 platform. Eleven ATXN3 mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 58 publications
3
30
0
Order By: Relevance
“…For SCA3, higher blood NfL levels were found in young mutation carriers (Garcia-Moreno et al, 2022).…”
Section: Genetic Ataxiamentioning
confidence: 97%
See 1 more Smart Citation
“…For SCA3, higher blood NfL levels were found in young mutation carriers (Garcia-Moreno et al, 2022).…”
Section: Genetic Ataxiamentioning
confidence: 97%
“…The effect sizes were smaller for SCA1 ( n = 23) compared to healthy controls ( n = 25, 1.00; 95% CI 0.39–1.60); Friedreich ataxia ( n = 217) compared to healthy controls ( n = 62, 0.62; 95% CI 0.21–1.03) and SCA2 ( n = 16) compared to healthy controls ( n = 22, 0.59; 95% CI 0.27–0.91) (Peng et al, 2022). For SCA3, higher blood NfL levels were found in young mutation carriers (Garcia‐Moreno et al, 2022).…”
Section: Meta‐analysesmentioning
confidence: 99%
“…Because clinical trials for SCA3 are routinely preceded by preclinical assays and interventions conducted in mouse models of this disease, it is essential that these models show biofluid biomarkers and biomarker changes like patients with SCA3. Hence, we sought to evaluate whether aged SCA3 YACQ84 transgenic mice expressing the full-length human ATXN3 disease gene (Cemal et al, 2002), frequently used in preclinical trials for SCA3 (Rodriguez-Lebron et al, 2013b, Ashraf et al, 2019, McLoughlin et al, 2018, Moore et al, 2017, Costa et al, 2013, replicate the increased blood NfL levels observed in patients with SCA3 (Wilke et al, 2020b, Li et al, 2019, Wilke et al, 2018, Peng et al, 2022, Garcia-Moreno et al, 2022, Coarelli et al, 2021.…”
Section: Aged Homozygous Yacq84 Transgenic Mice Show Increased Levels...mentioning
confidence: 99%
“…In particular, NfL has been evidenced to hold notable value as a biomarker for SCA3. Patients with SCA3 exhibit significantly higher levels of NfL in serum, plasma, and CSF compared to healthy controls (Wilke et al, 2020b, Li et al, 2019, Peng et al, 2022, Garcia-Moreno et al, 2022, Coarelli et al, 2021, Prudencio et al, 2020, Wilke et al, 2018. Remarkably, SCA3 carriers in pre-ataxic stages also show increased abundance of NfL in biofluids with proximity to age of onset of clinical ataxia presentation (Wilke et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…23 Furthermore, plasma t-tau elevation is not specific in AD, and is also found in several other neurodegenerative diseases. 24 CSF NfL is one of the most promising neurodegenerative biomarkers. Notably, plasma NfL corresponds well to CSF measures, making it a good blood-based biomarker.…”
mentioning
confidence: 99%